Digital Creativity Individuals, Groups, and Organizations - Lee, Kun Chang (Integrated Series in Information Systems, 2013)
As the use of digital technology has grown, so necessarily has the body of research into its effects at the personal, group and organizational levels, but there is no one book that looks at how digital technology has specifically influenced creativity.  Digital Creativity: Individuals, Groups, and Organizations discusses all spectrums of influence that digital technologies have on creativity from the individual, team, and organization level. This book offers a new kind of creativity model encompassing all three levels of creativity.  It combines each level into a unified creativity framework in which organizations regardless of their industry types could benefit in reengineering their business processes as well as strategies. For this purpose, the book considers various factors that would affect creativity- individuals' digital efficacy, heterogeneity among members (i.e., age, gender, races, tenure, education, and culture, etc), CMC (Computer-Mediated Communication), task complexity, exploitation, exploration, culture, organizational learning capability, and knowledge networks among members. This book introduces a theorized and systematic glimpse into the exciting realm of digital creativity.  It is organized with contents starting from individuals to teams and ultimately to organizations, each with various techniques and cases. Each chapter shows how individuals, teams, and organizations can become more creative through use of digital technologies.